Design and Performance of Microstrip Diplexers: A Review - Yahya, Salah I.; Rezaei, Abbas; Nouri, Leila (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
The radiofrequency microstrip diplexers are widely demanded nowadays by modern wireless communication systems. Hence, several types of previously reported microstrip diplexers are reviewed and investigated in this work. Microstrip diplexers are three ports devices used for separating desired signals and delivering them through two (or more) different channels. The diplexers are investigated in three categories of dual-channel bandpass-bandpass diplexers, multichannel diplexers, and lowpassbandpass diplexers. The investigated multi-channel diplexers include a number of four-channel, six-channel, and eight-channel diplexers. Due to the hard design process, the number of reported diplexers with more than four channels is limited. The layout structures and theory design methods of the previously reported diplexers are studied. Moreover, their size and performance are compared while some explanations about their advantages and disadvantages are presented. This comparison includes insertion loss, return loss, fractional bandwidths, isolation, selectivity, and gaps between channels.